Modelling of charge injection by multi-photon absorption in GaN-on-Si HEMTs for SEE testing. (November 2021) - Ngom, C.; Pouget, V.; Zerarka, M.; Coccetti, F.; Crepel, O.; Touboul, A.; Matmat, M.
Abstract: This paper presents the numerical evaluation of different multiphotonic absorption mechanisms to be used for backside laser testing of single-event effects in GaN-on-Si HEMTs. The optical transmission through the complete stack of layers of three commercial references is calculated. Experimental results illustrating the possibility to use three-photon absorption for charge injection in the GaN layer are presented. The possible contribution of higher-order optical absorption in the buffer layers is discussed. Highlights: Wide Band Gap technologies such as GaN HEMTs have encountered significant interest for several applications Mechanisms involved in Single event effects (SEE) on these devices need to be further understood Laser testing for SEE characterization of commercial GaN devices presents a major interest